Correlation of the score for subjective pain with physical disability, clinical and radiographic scores in recent onset rheumatoid arthritis - Turiel Maurizio; Panni Benedetta; Fiorini Tania; Sarzi-Puttini Piercarlo; Cazzola Marco; Atzeni Fabiola (BMC Musculoskeletal Disorders, 2002)
Abstract Background To analyse the relationship between subjective pain score and other measures of clinical, radiographic and functional status; in particular Larsen radiographic scores and Health Assessment Questionnaire (HAQ); in patients with severe rheumatoid arthritis (RA) with a disease duration of less than 3 years. Methods In this cross sectional study of 105 patients with RA (76 women, 29 men: mean age 50.93; mean disease duration 15.86 months; 71% rheumatoid factor positive) subjective pain was assessed according to the Visual Analog Scale (VAS). Correlation coefficients between pain score and disease activity measures (patients' global assessment of disease by VAS, number of tender and swollen joints, morning stiffness, erythrocyte sedimentation rate [ESR], C-reactive protein [CRP] and titre of rheumatoid factor, radiographic evaluations (Larsen-Dale scores for radiographic damage of the small joints of the hands, wrist and feet), disability measures (health assessment questionnaire [HAQ]), and demographic variables were calculated; hierarchical regression analysis was done with subjective pain score as the dependent variable. Results The Spearman's correlation coefficient comparing subjective pain and HAQ was 0.421 (p < 0.001), between subjective pain and global assessment of disease and morning stiffness was 0.573 (p < 0.001) and 0.427 (p < 0.001) respectively, and between pain and number of tender and swollen joints 0.037 and 0.050 respectively (p > 0.05). In regression analysis, global assessment of disease by patients explained 32.8% of the variation in pain intensity score, morning stiffness 10.7%, CRP 4.0%, HAQ 3.8% and Larsen-Dale scores explained 2.1%; other variables were not significant in the model. Conclusions Pain scores of patients with early severe rheumatoid arthritis are correlated at higher levels with patients' global assessment of disease and with morning stiffness rather than with radiographic or other clinical variables such as number of tender and swollen joints.